The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acssynbio.8b00415
|View full text |Cite
|
Sign up to set email alerts
|

Stationary Patterns in a Two-Protein Reaction-Diffusion System

Abstract: Patterns formed by reaction-diffusion mechanisms are crucial for the development or sustenance of most organisms in nature. Patterns include dynamic waves, but are more often found as static distributions, such as animal skin patterns. Yet, a simplistic biological model system to reproduce and quantitatively investigate static reactiondiffusion patterns has been missing so far. Here, we demonstrate that the Escherichia coli Min system, known for its oscillatory behavior between the cell poles, is under certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 36 publications
7
76
0
Order By: Relevance
“…Our in vitro experiments in laterally wide, flat microchambers with a well-controlled finite height showed that the Min-protein interactions can yield dramatically different patterns by changing only the height of the confining chamber and the E:D ratio. While the important role of total densities as control parameters was shown before (both in theoretical (37,39,52) and experimental (23,27) studies) our findings show that the bulk height, or more generally the bulk-surface ratio, is an equally important control parameter. This parameter determines how far concentration gradients can penetrate into the cytosol in the direction normal to the membrane.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our in vitro experiments in laterally wide, flat microchambers with a well-controlled finite height showed that the Min-protein interactions can yield dramatically different patterns by changing only the height of the confining chamber and the E:D ratio. While the important role of total densities as control parameters was shown before (both in theoretical (37,39,52) and experimental (23,27) studies) our findings show that the bulk height, or more generally the bulk-surface ratio, is an equally important control parameter. This parameter determines how far concentration gradients can penetrate into the cytosol in the direction normal to the membrane.…”
Section: Discussionsupporting
confidence: 57%
“…The Min system was discovered in E. coli (14,15), and subsequently purified and reconstituted in vitro on supported lipid bilayers that mimic the cell membrane (16). This reconstitution provides a minimal system that enables precise control of reaction parameters and geometrical constraints (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). This enabled the study of the patternformation process and its molecular mechanism in a well-controlled manner, and showed the ability of the Min system to form a rich plethora of dynamic patterns, predominantly travelling waves and spirals, but also "mushrooms", "snakes", "amoebas", "bursts" (16,17,28) as well as quasi-static labyrinths, spots, and mesh-like patterns (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…The repeated switching of MinD polarity due to redistribution of MinE is what gives rise to the Min oscillations in E. coli. Recently also stationary Min patterns have been observed in vitro (Glock et al, 2019). Conversely, oscillatory Cdc42 dynamics are found in the fission yeast S. Pombe , and have also been indirectly observed in budding yeast mutants Ozbudak et al, 2005).…”
Section: Rescue Mechanism: Cdc42 Transport Plus Polar Gap Saturationmentioning
confidence: 91%
“…We expect that the insights obtained from the minimal two-component model studied here generalize to systems with more components and multiple protein species. For example, in vitro studies of the reconstituted MinDE system of E. coli show that MinD and MinE spontaneously form dynamic membrane-bound patterns, including spiral waves [48] and quasi-stationary patterns [49]. These patterns emerge from the competition of MinD self-recruitment and MinE-mediated detachment of MinD [50,51].…”
Section: Discussionmentioning
confidence: 99%